The Role of Accountants in Encountering Climate Change and Its Impact on the Industrial Sector Companies Sustainability: A Conceptual Model - Winarsih WINARSIH; Khoirul FUAD; Luluk Muhimatul IFADA; Maya INDRIASTUTI (Communications of International Proceedings, 2022)
Climate change is a big issue and impacts the business sustainability of industrial companies that depend on fossil fuel energy. The current climate change condition is still an externality that has not been considered by the government, private, and community sectors. Accordingly, it has not been fully anticipated and realized by the three sectors. Internalization of climate change issues has not been reflected in the financial statement accounts due to the difficulty in measuring the potential of climate change to the company's operations in the future. One of the criteria used by accountants in determining whether information should be reflected in the financial statements is materiality. An information has materiality if the negligence of the information in the financial statements will change the decisions taken. This research is expected to contribute ideas on how an accountant handles climate change issues in financial reports by looking at the applicable Indonesia Accounting Standards (PSAK). It aims to reflect climate change issues in financial statements. The research method used is narrative analysis to describe the past, current, and other events. Finding the causes of climate change and its impacts will contribute to the accounting profession tackling climate change issues.
Keywords: climate change; environmental accounting; financial statement; materiality